2011
DOI: 10.1007/s11916-011-0213-3
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disorders and Fibromyalgia

Abstract: Disordered sleep is such a prominent symptom in fibromyalgia that the American College of Rheumatology included symptoms such as waking unrefreshed, fatigue, tiredness, and insomnia in the 2010 diagnostic criteria for fibromyalgia. Even though sleep recording is not part of the routine evaluation, polysomnography may disclose primary sleep disorders in patients with fibromyalgia, including obstructive sleep apnea and restless leg syndrome. In addition, genetic background and environmental susceptibility link f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 90 publications
4
44
0
2
Order By: Relevance
“…It has been suggested that in FMS, increased sympathetic activity in CNS and release of proinflammatory cytokines from glial cells adversely affects sleep quality. On the other hand, sleep has been suggested to have an impact on fibromyalgia symptoms, with an underlying immunological pathogenesis, and effects of mediator cytokines, such as TNF-α and IL1-β, involved in the sleep regulating regions of CNS on the the emergence of FMS symptoms have also been indicated [23]. In our study, complaints of sleep disorders were found in similar patients with FMS and OSAS.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…It has been suggested that in FMS, increased sympathetic activity in CNS and release of proinflammatory cytokines from glial cells adversely affects sleep quality. On the other hand, sleep has been suggested to have an impact on fibromyalgia symptoms, with an underlying immunological pathogenesis, and effects of mediator cytokines, such as TNF-α and IL1-β, involved in the sleep regulating regions of CNS on the the emergence of FMS symptoms have also been indicated [23]. In our study, complaints of sleep disorders were found in similar patients with FMS and OSAS.…”
Section: Discussionsupporting
confidence: 62%
“…Patients with AHI of ≥5 events/h were diagnosed with OSAS. Based on their AHI scores, the patients were categorized into mild (AHI, 5-15), moderate (AHI, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], and severe OSAS (AHI, >30) groups according to the AASM Task Force criteria [11]. Oxygen desaturation index (ODI) was defined as the total number of measurements of oxyhemoglobin desaturation of ≥4% within ≥10 s-<3 min from the baseline divided by the total sleep time.…”
Section: Psg Evaluationmentioning
confidence: 99%
“…Sleep disorders like obstructive sleep apnea and restless legs syndrome appear to be more common in patients with FMS, particularly in male patients, than in the general population [151][152][153][154][155][156], and FMS may be more prevalent among patients with sleep apnea than in the general population [157]. The presence of such sleep disorders is associated not only with worse perceived sleep quality, but also with pain, fatigue, and greater symptoms severity (assessed with the Fibromyalgia Impact Questionnaire, FIQ) [151,156].…”
Section: Sleepmentioning
confidence: 96%
“…It is essential to incorporate sleep medicine in the core curriculum of any perioperative fellowship program because it has relevance in multiple areas of anesthesia, such as out-of-OR sedation, perioperative airway management with positive airway pressure techniques, and as a comorbidity in the management of pain-related disorders. 42,61 With respect to other respiratory conditions, cigarette smoking continues to be prevalent in the surgical population. Effective preoperative counselling on smoking cessation is not emphasized in residency curricula.…”
Section: Discussionmentioning
confidence: 99%